Anthrax in the South of Russia - F. V. Logvin; A. N. Kulichenko; A. G. Ryazanova; D. K. Gerasimenko; E. I. Eremenko; K. A. Oleynikova; L. Yu. Aksenova; O. V. Semenova; A. V. Nikitina; T. M. Golovinskaya; G. А. Pechkovskii (Медицинский вестник Юга России, 2024)
Objective: analysis of the current epizootological and epidemiological situation on anthrax and characteristic of stationary hazardous for this infection areas (SHAs) in the South of Russia.Materials and methods: we used data on SHAs and anthrax burials from the Rospotrebnadzor Directorates for the subjects of the Southern (SFD) and North Caucasus (NCFD) federal districts, regional Veterinary Directorates, official data from Rospotrebnadzor and Rosselkhoznadzor on morbidity in humans and livestock.Results: anthrax is almost ubiquitous in the regions of the SFD and NCFD. According to data updated in 2023, in the South of Russia, 3845 SHAs were taken into account, in which 9815 outbreaks were registered. In 1999-2023 92 SHAs showed activity, 23 of which are new. There are 350 anthrax burials located in the SHA’s territories. Over 25 years, there were 104 outbreaks affecting at least 269 livestock and 134 people, with 4 deaths. Human infection occurred mainly during the forced slaughter of sick cattle, unvaccinated against anthrax, through contact with contaminated meat.Conclusion: the epidemiological and epidemiological situation on anthrax in the South of Russia continues to remain unstable. The problem is due to the presence of a significant number of soil hotspots against the backdrop of incomplete implementation of preventive measures. Stabilization of the anthrax situation can only be achieved by implementing a full range of preventive and anti-epidemic measures in the format of interdepartmental interaction.